2020
DOI: 10.1186/s10020-020-00206-x
|View full text |Cite
|
Sign up to set email alerts
|

Chorioamnionitis induces enteric nervous system injury: effects of timing and inflammation in the ovine fetus

Abstract: Background: Chorioamnionitis, inflammation of the chorion and amnion, which often results from intrauterine infection, is associated with premature birth and contributes to significant neonatal morbidity and mortality, including necrotizing enterocolitis (NEC). Recently, we have shown that chronic chorioamnionitis is associated with significant structural enteric nervous system (ENS) abnormalities that may predispose to later NEC development. Understanding time point specific effects of an intra-amniotic (IA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
5
7
0
Order By: Relevance
“…LPS-induced chorioamnionitis was observed to cause a biphasic decrease in goblet cell counts. The first reduction coincided with early systemic inflammation 24 h after IA LPS exposure (IL6) [2] and intestinal inflammation at 24 h (IL8) [31] and 2 d (macrophages) (Heymans et al submitted for publication) after IA LPS exposure that we observed in earlier published studies of the same experiment. It is therefore probably caused by emptying of goblet cell secretory vesicles as a natural response to acute inflammation [29].…”
Section: Discussionsupporting
confidence: 71%
“…LPS-induced chorioamnionitis was observed to cause a biphasic decrease in goblet cell counts. The first reduction coincided with early systemic inflammation 24 h after IA LPS exposure (IL6) [2] and intestinal inflammation at 24 h (IL8) [31] and 2 d (macrophages) (Heymans et al submitted for publication) after IA LPS exposure that we observed in earlier published studies of the same experiment. It is therefore probably caused by emptying of goblet cell secretory vesicles as a natural response to acute inflammation [29].…”
Section: Discussionsupporting
confidence: 71%
“…8C,D) after IA LPS administration, compared to control (Fig. 8A,D), which supports and extends earlier findings 24,28 . Moreover, ileal IL-18 mRNA levels tended to be increased 24 hours after IA LPS administration, compared to control (P = 0.07; Fig.…”
Section: Resultssupporting
confidence: 92%
“…Although hepatic TNF-α , IL-8 and IL-18 levels have all been normalized at day 4 after IA LPS administration and no alterations in extramedullary hematopoiesis were observed until day 8 after IA LPS administration, it is possible that the early hepatic cytokine response contributed to the altered fetal erythropoiesis at day 8 and day 15 after IA LPS administration. In addition, fetal ileal inflammation was observed in the current and previous studies 24 with the most evident signs of inflammation 2 days and 4 days after IA LPS exposure. Transport of inflammatory mediators from the gut to the liver via the portal vein may therefore also contribute to hepatic inflammation, illustrated by extramedullary hematopoiesis.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations